Edith Mirrielees - unknown:::Creator::::::::::::
Edith Mirrielees as a student. Ms. Mirrielees (front row, 2nd from left) was Steinbeck's favorite teacher when he was at Stanford. Photo shows Mirrielees with other board members of Stanford Quad.